Prevalence of Ectoparasites in Tilapia (Oreochromis niloticus) in Tarakan - Ihsan, Burhanuddin; Sitinjak, Rini Septriananda (Jurnal Medik Veteriner, 2023)
Freshwater fisheries product tilapia (Oreochromis niloticus) has the potential to be developed and has a very high economic value, particularly in the city of Tarakan. Fish ectoparasites are a problem that frequently occurs and is discovered in aquaculture. This study aimed to determine the type of ectoparasites that infect tilapia in aquaculture ponds in Kampung Satu and Sebengkok. The technique involved collecting tilapia samples from various ponds and then transporting them to the laboratory. A total of 30 samples were taken from the container that was set up on a tray, and they were all put to death by being stabbed in the brain nerves. It was done to identify ectoparasites on the gills, eyes, scales, and fins of the fish. Two forms of ectoparasites, Dactylogyrus sp. and Trichodina sp., which were only present in the gills, were identified in the tilapia. In the moderate infection group, the prevalence rate in Kampung Satu was 86%, and in the very frequent infection category, it was 66% in Sebengkok. In Kampung Satu, the level of ectoparasites was 3,84, which is considered low, and 8,30, which is considered medium, in Sebengkok.